Encyclopedia of homelessness - Levinson, David, 1947- (Thousand Oaks, Calif. : SAGE Publications, 2004)
'The first comprehensive resource on this important topic, this set covers the origins of homelessness, current research, and strategies for its prevention. The contributors represent such disciplines as sociology, anthropology, medicine, and social work. Articles address homelessness in eight major American cities and more than 30 cities and nations around the world. Adding depth are bibliographies, a directory of street newspapers, a filmography, and more than 20 primary-source documents offering historical and contemporary perspectives.'--'Reference that rocks,' American Libraries, May 2005
'A Berkshire Reference Work.'
'A Sage Reference Publication.'
Keywords: Homelessness -- Encyclopedias